Palladium Catalyzed Synthesis and Functional Groups Modification of 6-Aryl Derivatives of Non-Linear Azaphenothiazinones - E.L, Ayuk; S.U, Ilo; C. M, Nweke; I. C, Onunkwo (International Journal of Chemistry and Materials Research, 2016)
This report presents the synthesis of four derivatives of 6-chloro-11-azabenzo[a]phenothiazine-5 one, of the type 15,16,17 and 18 .The starting material, 2-aminopyridine 8 was subjected to thiocynation and subsequently, to hydrolysis to furnish one of the key intermediates, 2 aminopyridine-3-thiol 10 .This was condensed with 2,3-dichloro-1,4-naphthoquinone 11 to yield 6 chloro-11-azabenzo[a]phenothiazinone 5. In the presence of a complex palladium catalyst system, compound 5 was coupled with arylphenylboronic acids, 6 and 7 to give 6-phenyl-11 azabenzo[a]phenothiazine-5-one 15 and 6-(3-nitrophenyl)-11-azabenzo[a]phenothiazine-5-one, 16 respectively. Reduction of the nitro-group in 16, furnished 6-(3-aminophenyl)-11 azabenzo[a]phenothiazine-5-one 17, while the oxidation of the amino-group in compound 17, produced 6-(3-hydroxyphenyl)-11-azabenzo[a]phenothiazine-5-one 18. Treatment of the above compounds 15, 16 ,17 and 18 respectively, with sodium dithionite gave color discharged unstable basis of the types 19, 20, 21 and 22 which could not be isolated, but reverted to the original compounds 15, 16,17 and 18 above immediately they were exposed to air. This property suggests that they can be used as vat dyes.